Bacteriological Quality Assessment of Cosmetic Products Sold in Yola, Adamawa State Nigeria - Kachalla, Nafisat Adamu; Isa, Halima; Bashir, Mohammed; Sahabo, Saadatu A (The Asia Journal of Applied Microbiology, 2022)
Cosmetics products are external preparations normally applied to human body parts mainly for beautification. These products are potential reservoirs of infection due to contamination by microbes. The bacteriological quality of different cosmetic products sold within Yola, Adamawa state Nigeria was determined by isolation and antibiotic susceptibility profiling of bacterial isolates. The work was conducted at the Department of Microbiology, Modibbo Adama University Yola Adamawa state Nigeria between February 2021 and July 2021. A total of 30 samples from 5 different categories of cosmetics (powder, mascara, foundation, lipstick and body cream) were assessed. Detection and identification of bacteria were carried out using standard microbiological techniques. Bacterial load was determined by direct colony count and the antibiotic susceptibility profile of each isolates was determined following the Kirby-Bauer disc diffusion method using fourteen antibiotics. Out of the 30 samples analyzed, 86.5 % were contaminated, with bacterial load ranging from 1.0 x 103 to 20.0 x 103 cfu/g. Bacterial isolates obtained includes Staphylococcus aureus (42.3 %), Escherichia coli (23 %) Pseudomonas aeruginosa (15.3 %), Klebsiella (7.7 %) and Salmonella (11.5 %). Antibiotic susceptibility testing indicated that isolates of Pseudomonas aeruginosa were mostly resistant. It was depicted that resistance to Chloramphenicol and tetracycline was 100 % while a significant number of the isolates were sensitive to Rifampicin, Amoxicillin and Norfloxacin. The various cosmetics found on the shelves of Yola market are contaminated with different pathogenic bacterial species with different occurrence rate as well as susceptibility pattern.